Cutaneous manifestations of COVID-19 infection - Vargas-Machuca Carranza, Christian Alberto (2021)
We present the case of a 45-year-old patient who started with non-productive cough, general malaise and progressive dyspnea, confirming the diagnosis of severe COVID-19 with a favorable response to treatment. In the clinical evolution, he presented itchy papulovesicular lesions that resolved spontaneously over the course of the weeks.